The Effect of Remittances on Indonesia’s Economic Growth and Exchange Rate - Annisa, Rahma (Animo Repository, 2024)
This study aims to measure the effect of remittances by Indonesian workers from abroad on Indonesia’s economic growth and exchange rate. This study uses the vector autoregression (VAR) model to see the interrelationship between the variable and the error-correction model (ECM) in the short term and the long term. The results show no causal relationship between remittances and economic growth in Indonesia. Remittances have also proven to have no effect on Indonesia’s economic growth, both in the short and long term. The Granger causality test on remittances has been proven to affect the exchange rate significantly. However, there is no short-term or long-term relationship between remittances and exchange rates. This is because the remittances received by Indonesia can still be classified as small. Hence, they are not able to sustain Indonesia’s economic growth and exchange rate.